Harmonisasi Regulasi Kewenangan Badan Pemeriksa Keuangan untuk Meminta Dokumen Pihak Ketiga dalam Pelaksanaan Pemeriksaan Keuangan Negara: Regulatory Harmonization of the Authority of the Audit Board to Request Third-Party Documents in State Financial Audits - Devitri, Salsa (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2025)
State financial audits are a vital instrument for ensuring accountability and transparency in public financial management. Legally speaking, the Audit Board (BPK) is authorized to request documents from third parties. This study aims to analyze the harmonization of regulations governing BPK's authority to request third-party documents in the implementation of state financial audits. This study employs a normative juridical method that incorporates statutory and conceptual approaches. The findings indicate that the BPK's authority to request third-party documents is often constrained by overlapping sectoral regulations, including those governing personal data protection, banking, tourism, and transportation. This situation creates legal uncertainty and hampers audit effectiveness; regulatory harmonization is required. To do so, the lawmakers need to adopt a new bridging regulation that recognizes the BPK’s authority as a particular exception to sectoral restrictions when auditing state finances and that establishes standards for data protection and the confidentiality of audit work papers. Such regulatory harmonization is crucial for strengthening professionalism, accountability, and transparency in the oversight of state financial management while simultaneously upholding the principles of good governance.